Prevalence and determinant of depression symptoms in aged people attended in primary health attention - Fernandes, Maria das Graças Melo; Nascimento, Neilce Falcão de Souza; Costa, Kátia Nêyla de Freitas Macêdo (Rev Rene, 2010)
This exploratory study aims to identify the prevalence and determinant of depression symptoms in aged people attended in primary health attention. Its effectiveness was in a Family Health Unit in the city of João Pessoa – PB, from February to June of 2006, involving a population of 91 aged people. The collection of data was accomplished by an interview, with the use of a structured instrument. The empirical information was quantitative analyses. The results point to a prevalence of depression between 52% of the researched aged people. Taking into consideration the determinant, we observed similar data with the pertinent literature, with multiple etiological events standing out. As far as the biological factors are concerned, we verifi ed old age, feminine gender, and presence of physical diseases and use of medicine. Between the psychological and social events starters of depression in the investigated group, we observed low level of rent and schooling, defi cit of the social support and loss of a relative, especially of the partner.